2000
DOI: 10.1117/12.386335
|View full text |Cite
|
Sign up to set email alerts
|

<title>Local determination of hemoglobin concentration and degree of oxygenation in tissue by pulsed photoacoustic spectroscopy</title>

Abstract: Pulsed-photoacoustic spectroscopy (PPAS) in the near-infrared portion of the optical spectrum was used as a local technique for quantitative monitoring of tissue hemoglobin concentration and its oxygenation state. A pulsed, tunable optical source coupled to a 1mm-diameter optical fiber cable was used to deliver optical energy to the tissue under study. The fiber was placed either on the exterior surface or inserted into the tissue. An ultrasonic signal was produced in the tissue as a result of the absorbed lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 7 publications
0
24
0
6
Order By: Relevance
“…Using a low frequency ultrasound detector (<1 MHz), Fainchtein et al 62,63 made measurements of the wavelength dependence of the amplitude of the peak of the PA wave which showed qualitative agreement with the absorption spectrum of blood (710 to 870 nm), both for blood in a cuvette and in a canine arterial-venous shunt. The measured spectrum changed approximately as expected as the level of oxygen in the blood was varied, but no quantitative estimates were made.…”
Section: Cuvette Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a low frequency ultrasound detector (<1 MHz), Fainchtein et al 62,63 made measurements of the wavelength dependence of the amplitude of the peak of the PA wave which showed qualitative agreement with the absorption spectrum of blood (710 to 870 nm), both for blood in a cuvette and in a canine arterial-venous shunt. The measured spectrum changed approximately as expected as the level of oxygen in the blood was varied, but no quantitative estimates were made.…”
Section: Cuvette Measurementsmentioning
confidence: 99%
“…Subsequently μ eff was measured from the slope of the curve, and μ 0 s calculated from it, by use of the known μ a . Rather than measuring the diffuse reflectance, Fainchtein et al 62,63 modeled it as approximately R d∞ ≈ expð−7μ a ∕μ eff Þ. Note that in both cases an additional optical measurement, or an additional assumption, is required to allow both μ a and μ 0 s to be estimated from the PA signal.…”
Section: Homogeneous Scattering Mediummentioning
confidence: 99%
“…By taking advantage of the ultrasonic detection, PA imaging can provide better spatial resolution than DOI. In addition, by leveraging the intrinsic oxygen-dependent spectral absorption properties of hemoglobin, it has been shown that this technique can detect changes in SO 2 and total hemoglobin concentration (HbT) related to blood volume and flow independently in single vessels (Fainchtein et al, 2000). This is a fascinating feature for a label-free functional brain imaging system.…”
Section: Introductionmentioning
confidence: 98%
“…Photoacoustic detection of deeply embedded absorbing objects colored with bovine hemoglobin was achieved by Esenaliev et al 9 More recently, Kolkman et al 12 explored the photoacoustic imaging of blood vessels in human skin. Fainchtein et al 17 studied photoacoustic measurements on in vitro and in vivo blood samples and proved that this technique can assess relative changes in concentrations of both oxygenated hemoglobin ͑HbO 2 ͒ and deoxygenated hemoglobin ͑Hb͒. Single-wavelength photoacoustic detection was used by Esenaliev et al 18 to monitor relative changes in blood oxygenation in vitro.…”
Section: Introductionmentioning
confidence: 99%